Contacts Between Arab Communists and the Communist Party of France in the 1950s and 1960s and The Limitations of Cultural Transfer - Hannová, Daniela (Dějiny – teorie – kritika, 2015)
Arab communist parties have been maintaining strong contacts with their European counterparts since the beginning of the 20th century. What they sought was not only advice but also real political support. This study analyses mutual communication between Arab and French communists using the archive documents of the Communist Party of France from the 1950s until late the 1960s. Attempts to outline the origins of Arab communist parties are limited by lack of relevant academic studies. This contribution is based mainly on archive materials of the Communist Party of France. Correspondence, newspaper articles, and reports describing mutual visits and encounters at regular meetings of the communist parties form the main basis on which one can outline the limits of cultural transfer of communist ideology in the Arab world. Repeated emphasis on national values and the use of religious symbolism by Arab communists reveals some particular values shared across the Middle Eastern political spectrum. Certain specific features of leftist Arab movements can be seen as manifestations of post-colonial values of modern Arab societies, persisting despite the strong influence of European communism.